The factors affecting bank profitability: The case of Bosnia and Herzegovina - Alihodžić, Almir (Czynniki wpływające na rentowność banków: przypadek Bośni i Hercegowiny, 2020)
This research includes all banks in Bosnia and Herzegovina (B&H) and testing internal and external variables on bank profitability indicators. The primary goal of this paper is to determine, through correlation and regression analysis, the strength and significance of the external and internal variables on bank profitability in Bosnia and Herzegovina. Likewise, data were collected from quarterly reports of the Banking Agency of the Federation of B&H and the Banking Agency of the Republika Srpska for the period 2008 Q1 to 2019 Q4. The following dependent variables were used: ROA, ROE and independent variables: GRNGL, GRNPL, GRGDP, concentration ratio of loans of the largest banks in the system (CR Loans), concentration ratio of deposits of the largest banks in the system (CR Deposits), CAR and loan-to-deposit ratio. The study found that there is a significant statistical impact of the variables on ROA and ROE. In addition, this study points out the need for banks to properly select debtors, and control costs, toxic loans and provisions in order to increase profits and reduce costs
Financial Sciences. Nauki o Finansach, 2020, vol. 25, no. 2-3, s. 1-23
Keywords: profitability indicators; non-performing loans; concentration ratio; loan-to-deposit ratio; wskaźniki rentowności; kredyty zagrożone; wskaźnik koncentracji; stosunek kredytów do depozytów